2000
DOI: 10.21608/ejabf.2000.1650
|View full text |Cite
|
Sign up to set email alerts
|

Food Habits and Ultrastructure of Gastric Mill of the Grapsid Crab, Metopograpsus Messor (Forskal, 1775) From the Red Sea, Egypt.

Abstract: D uring the present study, the stomach contents of a medium-sized grapsid crab, Metopograpsus messor (Grapsidae, Brachyura) inhabiting different habitats (rocky, sandy-rock, and mangrove swamps) of the Red Sea (southern Aqaba Gulf) were examined by both frequency occurrence and percentage points. The results show that this species is opportunistic omnivore, with general food items consisting of algae (brown, red, green and blue green), benthic animals dominated by crustacean copepods, isopods, amphipods and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The trophic relationship observed in this study identified a unique trait associated with M. messor as the crab is generally considered an opportunist detritivore, herbivore and omnivore but not an active predator (El-Sayed et al ., 2000). Indeed, the results highlight that the prey-localizing and predatory fishing behaviour are not just opportunistic traits for a few specimens but are an established pattern for the entire population (Figure 5D).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The trophic relationship observed in this study identified a unique trait associated with M. messor as the crab is generally considered an opportunist detritivore, herbivore and omnivore but not an active predator (El-Sayed et al ., 2000). Indeed, the results highlight that the prey-localizing and predatory fishing behaviour are not just opportunistic traits for a few specimens but are an established pattern for the entire population (Figure 5D).…”
Section: Discussionmentioning
confidence: 99%
“…This characteristic has not been recorded in other Grapsid crabs (Fratini et al ., 2000; Linton & Greenaway, 2007; Poon et al ., 2010; Lee, 2015). Metopograpsus messor was observed predating not only A. d. dispar but also the shrimp P. khori and smaller M. messor demonstrating that the crab is more of a generalist predator rather than a specialist (El-Sayed et al ., 2000; Walton et al ., 2014). It is possible that a genetic trait has dominated this specific population of M. messor to evolve from opportunistic foragers to generalist hunters/fishers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations